Cover Feature: Room Temperature Decarboxylative and Oxidative [2+2+2] Annulation of Benzoic Acids with Alkynes Catalyzed by an Electron‐Deficient Rhodium(III) Complex (Chem. Eur. J. 2/2018). Issue 2 (25th October 2017) - Honjo, Yusaku; Shibata, Yu; Kudo, Eiji; Namba, Tomoya; Masutomi, Koji; Tanaka, Ken
Abstract : Room temperature decarboxylative annulation of benzoic acids with alkynes to produce substituted naphthalenes has been achieved by using an electron‐deficient (η5‐cyclopentadienyl)rhodium(III) [CpERhIII] complex. The electron‐deficient nature of the CpERhIII catalyst would cause the strong rhodium–π interaction, which accelerates the decarboxylation as well as the C−H bond cleavage. This low temperature carbon dioxide generation is compared to a beer dispenser. More information can be found in the Communication by Y. Shibata, K. Tanaka et al. onpage 317 .